Clinical and radiographic evaluation of autologous sticky bone versus PRF with OCP-coated deproteinized bovine bone graft in periodontal infrabony defect regeneration: a randomized controlled trial - Sakshi V. Kotecha; Priyanka Jaiswal; Shweta Bhagat; Pranjal Laturiya; Geeta Bhandari (BMC Oral Health, 2026)
Abstract Background Periodontal therapy aims to regenerate the attachment apparatus, including alveolar bone, periodontal ligament, and cementum. Infrabony defects are linked with periodontal progression if left untreated. To address limitations of conventional regenerative materials, Autologous Sticky Bone was developed, while Octacalcium Phosphate–Deproteinized Bovine Bone Material (OCP-DBBM) offers favorable conditions for capillary and osteogenic cell ingrowth. Methods Since comparative evidence is limited, this study evaluated the efficacy of Autologous Sticky Bone versus OCP-DBBM xenograft with A-PRF membrane in treating infrabony defects using CBCT. Twenty sites with systemically healthy subjects were equally allocated into Group A (Sticky Bone) and Group B (OCP-DBBM + A-PRF). Paired and unpaired Student’s t-tests were used for intra- and intergroup comparisons. Baseline measurements showed no significant differences. Results After 6 months, Group A demonstrated a PPD reduction of 2.6 ± 0.51 mm, while Group B showed 2.8 ± 0.78 mm. CAL improved to 4.3 ± 1.16 mm and 4 ± 1.15 mm, respectively. Radiographic defect depth reduced to 0.70 ± 0.39 mm (Group A) and 0.99 ± 0.41 mm (Group B). Conclusions Both approaches provided significant clinical and radiographic benefits. It can be stated that both regenerative approaches provided significant benefits regarding PPD reduction, CAL improvement, and radiographic defect depth reduction for infrabony defects. Trial registration The study was registered prospectively dated on 27/06/2024. URL: https://www.ctri.nic.in/Clinicaltrials/rmaindet.php?trialid=103894&EncHid=28647.22334&modid=1&compid=19